A influência de uma alimentação vegetariana no ganho de massa muscular - OLIVEIRA, Ricken John Puresa de (2024)
This narrative literature review addresses the trend towards including vegetarian diets in society and aims to investigate the influence of the ovolactovegetarian diet on mass gain slim. To this end, a search for scientific articles was carried out in the SciELO and PubMed databases. through the descriptors (“muscle mass gain” OR “muscular hypertrophy”) AND (“diet vegetarian” OR “dieta ovolactovegetarian” OR “vegetarian” OR “vegetarian diet” OR “aminocids” OR “history of vegetarianism”) covering publications from 2008 to 2023. Of the 46 selected works, only 12 met the inclusion criteria for the sample of study. The text explores different types of vegetarian diets and addresses muscle synthesis protein, emphasizing the importance of essential amino acids and their sources for synthesis, protein of vegetable origin and comparison with animal and possible difficulties in Synthesis of Muscle Protein (MPS) in vegetarians. The results indicate that in a diet balanced and with adequate supplementation of creatine, B12, BCAAs and iron for an MPS of quality, vegetarians can develop musculature at a similar rate to that of omnivorous individuals. Therefore, it is concluded that, with the supervision of a nutritionist, Vegetarians are able to overcome dietary limitations through supplementation and synthesize lean muscle with a balanced ovolactovegetarian diet, in addition to maintaining the chosen life.